Behavior Management in Pediatric Dentistry: An Overview and Interpretation - Burak Buldur (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2019)
In 1895, the first definition of behavior management was mentioned by McElroy with the following words: "although the operative dentistry may be perfect, the appointment is a failure if the child departs in tears”. This approach, which argues that the success of dental treatment in pediatric patients depends on the attitude created in children rather than in the technical or clinical evaluation, was supported by the following words in American Academy of Pediatric Dentistry (AAPD)'s guideline about 100 years later: “Behavior guidance techniques, both nonpharmalogical and pharmalogical, are used to alleviate anxiety, nurture a positive dental attitude, and perform quality oral health care safely and efficiently for infants, children, adolescents, and persons with special health care needs”. The terms of behavior management, which is the global term of choice, or behavior guidance which is now used by AAPD are widely used in dental literature.